Personal pronouns of mixtec: A comparative analysis between two linguistic variant - Rázuri Martínez, Ada R. (2017)
This article describes and compares the personal pronouns of the Mixtec Language of the linguistic variant of San Bartolomé Yucuañe, with the linguistic variant of Magdalena Peñasco. Both are located in the district of Tlaxiaco, Oaxaca, Mexico. These are the ways the languages classify their pronoun changes from one to the other. Thefirst, considersfactorssuchasgender, age, andfamilyand personal relationships. In the second variant of Mixtec, pronouns are only determined by the respect that is held with whom one is speaking. Considering these differences, we understand that these two variants of Mixtec have their unique way in using pronouns.